Health locus of control and health behaviour in Minangkabau metabolic disorder patients - Rida Yanna Primanita; Alfian Yanda Putra; Puput Nofia Rahma (International Journal of Public Health Science (IJPHS), 2026)
Metabolic disorders require sustained health behaviors, yet the psychological predictors of such behaviors may operate differently across cultures. This cross-sectional study examined whether health locus of control (HLOC) predicts multidimensional health behavior among Minangkabau adults with self-reported metabolic disorders in West Sumatra, Riau, and Jambi. A total of 274 participants completed multidimensional HLOC and health behavior scales. Reliability testing, descriptive statistics, Pearson correlations, multiple linear regression, and one-way ANOVA based on dominant HLOC type were conducted. Internal and powerful-others HLOC positively predicted total health behavior, whereas chance HLOC was not significant; however, the overall explanatory power was small (R² = 0.048). Health behavior did not differ meaningfully across dominant HLOC types, with very small effect sizes across diet, sleep, smoking, risky beverage consumption, and exercise (η² < 0.02). These findings suggest that in a collectivistic Minangkabau context, health behavior may be shaped not only by personal control beliefs but also by family, authority, and community norms. The cross-sectional design and self-reported diagnoses limit causal and clinical inference. Family-based education, community leader involvement, and culturally adapted health campaigns are recommended.